IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 30 TAHUN 2019 TENTANG PENILAIAN KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR CAMAT KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Asmawati, Asmawati (STIA SATYA NEGARA PALEMBANG, 2022)
Research on the Implementation of Government Regulation Number 30 of 2019 Concerning Civil Servant Performance Evaluation at the Camat Office, Talang Kelapa District, Regency. Every organization has goals, one of the organizational means to achieve goals is the performance of employees in carrying out the tasks for which they are responsible, according to their respective positions and roles in the organization. The research used in this study uses qualitative methods. Data collected through observation, interviews, and documentation. Data analysis techniques are carried out by data reduction, data presentation and drawing conclusions. Based on the results of the research and discussion, it shows that the Implementation of Government Regulation Number 30 of 2019 Concerning Civil Servant Performance Evaluation at the Talang Kelapa District Office, Banyuasin Regency (Case Study Article 4) has been going well, as evidenced by the communication, disposition, and bureaucratic structure that is running well enough good while at work. Even though the visible resources are still lacking in work because there are still employees who arrive late and are not there when needed. But the tasks of each section have been carried out properly. Keywords: Implementation, PNS Performance Assessment